The Netherlands and European integration, 1950 to pPresent - Segers, Mathieu, author. Link
1 online resource.
Keywords: On 9 May 1950, France launched a revolutionary plan for supranational cooperation in Western Europe. The Netherlands was taken completely by surprise. In the decades that followed, European integration moved forward at an unprecedented pace, taking the Netherlands with it. Geography and the post-war world seemed to leave the country no other choice. European integration forced - and is still forcing - the Netherlands on a far-reaching 'journey to the continent'. For the Netherlands, European integration represents a difficult journey to a new old world that often seems far off. How has that journey progressed so far? Why did the Netherlands join the common European market and currency from the very beginning? Was this course inevitable? And where has it brought the country? Using new, international source material, The Netherlands and European Integration, 1950 to Present digs deeply into the history of the Netherlands in Europe - a subject that is today more topical than ever.